Descriptive, exploratory study of the role of nursing assistants in Australian residential aged care facilities: the example of pain management - Holloway, Kristi; McConigley, Ruth (Blackwell Publishing, 2009)
Aim: This study explored the experiences of nursing assistants (NAs) who work with older people in residential aged care facilities (RACFs), to ascertain their role in Australian RACFs. Experiences with pain management were used as an example to explore their work role. Methods: A descriptive, exploratory qualitative approach was used to examine NAs' experiences. Participants included six NAs from three RACFs in regional Western Australia. In-depth interviews focused on the NAs' experiences of providing care to older people in RACFs and in particular their experiences providing pain management for residents. Results: The role of NAs often extends beyond their scope of practice. NAs describe making clinical decisions, initiating clinical care and advocating for residents. Conclusions: NAs represent a majority of the staff in Australian RACFs and they have a significant role in clinical care. There is a need to ensure that NAs are adequately prepared and supported in their role.